Evaluation of thermodynamic perfection of the heating cascade machine cycles - Morozyuk, Larisa (Eastern-European Journal of Enterprise Technologies, 2016)
One of the promising trends in the refrigerating engineering is building machines for industrial processes with the simultaneous use of two thermal effects (heat and cold). The fundamental possibility to build machines, operating on a complex reverse thermodynamic cycle with the production of low-grade cold and high-grade heat is considered. Such machines are called heating cascade machines. The synthesis of cyclic machine solutions for various pairs of materials, based on thermodynamic analysis by the “method of cycles” is carried out. The analysis of the supercritical cycle of the upper cascade with R744 by the entropy-cycle method is performed. It is shown that the compound Carnot-Lorenz cycle (“triangular”) should be chosen as the cycle model. The problem of determining the degree of thermodynamic perfection of the cascade cycle, which takes into account the simultaneous production of two thermal effects – cold and heat is solved. An example of the calculation of the machine characteristics under variable input parameters: temperature in the condenser-evaporator and the pressure in the gas cooler is given. The comparison with the characteristics of the cascade machine, operating in the same mode, but with one thermal effect – the production of cold, which showed the benefits of heating cycles is performed. It is proved that, given the simultaneous high temperatures of the heat produced and low temperature of the cold produced in the cascade heating machine, energy performance is quite high. General recommendations – in terms of energy saving, heating cascade units and machines, operating with R744 as a working substance of the upper cascade and the cycle in the supercritical region with the simultaneous heat and cold production should be designed.